Electrolytic synthesis method of glyoxylic acid
By using diaphragm electrolytic cells and gas diffusion or membrane electrodes in glyoxylic acid electrolysis synthesis, we avoid the use of lead and iridium oxide anodes, reduce the electrolytic voltage, solve the problems of high cost and high energy consumption, and achieve higher product yields and environmentally friendly production.
Patent Information
- Application Number
- CN202410074873.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2025-07-18
AI Technical Summary
In the existing glyoxylic acid synthesis methods, the use of lead electrodes and iridium oxide anode leads to high costs and contamination, and the electrolytic energy consumption is high, and the life of the iridium oxide anode limits the production efficiency.
The membrane electrolytic cell is used, and hydrogen oxidation reaction is used as anode reaction, and the oxalic acid reduction reaction is a cathode reaction. The electrolysis is carried out through the gas diffusion electrode or membrane electrode. The lead and iridium oxide anode are avoided, and the electrolysis is carried out under the condition that the anode chamber pressure is not lower than the cathode chamber pressure to reduce the electrolytic voltage.
It significantly reduces the electrolytic energy consumption of glyoxylic acid, improves product yield, reduces production costs, and reduces pollutant emissions.
Smart Images

Figure BDA0004671111770000011 
Figure BDA0004671111770000041 
Figure BDA0004671111770000051
Abstract
Description
(1) Technical Field
[0001] The present invention relates to a method for electrolytic reduction synthesis of glyoxylic acid, belonging to the field of electrolytic synthesis. Specifically, it is a method for electrolytic reduction synthesis of glyoxylic acid with the oxidation reaction of hydrogen as the anodic reaction and the reduction reaction of oxalic acid as the cathodic reaction. (2) Background Art
[0002] The electrolytic reduction method of oxalic acid is an important method for the synthesis of glyoxylic acid, with advantages such as safety and high efficiency. In the electrolytic reduction method of oxalic acid for synthesizing glyoxylic acid, a lead electrode or an iridium oxide electrode is usually used as the oxygen evolution reaction anode. The lead anode has the advantages of low cost and convenient processing, but has problems such as a short service life (3 - 12 months), generation of a large amount of highly polluting lead mud, and high energy consumption. The iridium oxide anode (usually a titanium-plated iridium oxide electrode) is the best oxygen evolution anode, not only having a very low oxygen evolution overpotential but also very stable performance, but the price is relatively high. The service life of the iridium oxide anode is basically proportional to the iridium content on the electrode. The iridium oxide electrode with an iridium content of 10 g / m 2 Under a current density, the service life can reach about 2 years. Therefore, the loss of the iridium oxide anode is one of the main costs in the synthesis of glyoxylic acid by the electrolytic reduction method using the iridium oxide anode. At the beginning of 2021, the price of metallic iridium increased from 400 yuan / g to 1500 yuan / g and has since remained at a high level. This has imposed great investment cost pressure on the electrolytic reduction method of oxalic acid using the iridium oxide anode.
[0003] Therefore, there is an urgent need to develop an electrolytic synthesis method of glyoxylic acid that does not use a lead anode and an iridium oxide anode to replace the existing method. (3) Summary of the Invention
[0004] The purpose of the present invention is to provide an electrolytic synthesis method of glyoxylic acid, with the oxidation reaction of hydrogen as the anodic reaction and the reduction reaction of oxalic acid as the cathodic reaction. This method can not only avoid the use of a lead electrode and an iridium oxide anode, but also greatly reduce the electrolysis voltage and significantly improve the yield of glyoxylic acid.
[0005] The technical solution adopted by the present invention is:
[0006] The present invention provides an electrolytic synthesis method of glyoxylic acid, which uses a diaphragm electrolytic cell ( Figure 1 ), with the oxidation reaction of hydrogen as the anodic reaction, the reduction reaction of oxalic acid (B) as the cathodic reaction, an aqueous sulfuric acid solution as the anolyte, and an aqueous solution containing oxalic acid as the catholyte for electrolysis, and the electrolysis product in the catholyte is recovered to obtain the glyoxylic acid (A).
[0007]
[0008] Further, the pressure on the anolyte side of the diaphragm in the diaphragm electrolytic cell is greater than or equal to the pressure on the catholyte side of the diaphragm, and the pressure difference between the anolyte side and the catholyte side is 0 to 2 atm, preferably 0.01 to 2 atm.
[0009] Further, the pressure on the anolyte side is 1 - 3 atm.
[0010] Further, the anodic reaction occurs on a gas diffusion electrode or a membrane electrode.
[0011] Further, the gas diffusion electrode is composed of a gas diffusion layer and a catalytic layer. The gas diffusion layer is a porous carbon material or a metal material. The carbon material is carbon paper, carbon cloth, graphite felt, carbon felt or carbon foam, and the metal material is titanium or silver. The catalytic layer is composed of a platinum-carbon or palladium-carbon catalyst and a binder. The binder is polytetrafluoroethylene resin or Nafion resin or a mixture of both.
[0012] Further, the Pt or Pd loading of the gas diffusion electrode is 0.1 - 0.5 mg / cm 2 .
[0013] Further, the membrane electrode is composed of a gas diffusion layer, a catalytic layer and a cation exchange membrane. The catalytic layer is located between the gas diffusion layer and the cation exchange membrane. The gas diffusion layer is a porous carbon material or a metal material. The carbon material is carbon paper, carbon cloth, graphite felt, carbon felt or carbon foam, and the metal material is titanium or silver. The catalytic layer is composed of a platinum-carbon or palladium-carbon catalyst and a binder. The binder is polytetrafluoroethylene resin or Nafion resin or a mixture of both. The cation exchange membrane is a sulfonic acid type cation exchange membrane.
[0014] Further, the Pt or Pd loading of the membrane electrode is 0.1 - 0.5 mg / cm 2 .
[0015] Further, the diaphragm used in the diaphragm electrolytic cell is a cation exchange membrane or a microporous membrane, preferably a Nafion-324 membrane. The diaphragm electrolytic cell is divided into a gas chamber, an anodic chamber and a cathodic chamber by an anode and a diaphragm in sequence. The gas chamber is used to introduce hydrogen. An anode is arranged between the gas chamber and the anodic chamber, a diaphragm is arranged between the anodic chamber and the cathodic chamber, and a cathode is arranged inside the cathodic chamber. The cathode is made of a lead sheet. An aqueous solution containing 0.1 - 1.0 mol / L (preferably 0.5 mol / L) sulfuric acid is used as the anolyte. An aqueous solution containing 0.1 - 1.0 mol / L (preferably 0.68 mol / L) oxalic acid is used as the catholyte. Electrolysis is carried out under the conditions of 0 - 30 °C, a cathodic current density of 2.5 - 10 A / dm 2 , and an anodic current density of 5 - 20 A / dm 2 (preferably 10 °C, a cathodic current density of 5 A / dm 2, the anodic current density is 9.6 A / dm 2 ), the pressure of the anolyte is 1 - 3 atm, and the pressure difference between the anolyte and the catholyte is 0 - 2 atm.
[0016] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in: (1) The method for electrolytic reduction synthesis of glyoxylic acid in the present invention uses the oxidation reaction of hydrogen as the anodic reaction, preferably uses a membrane electrode or a gas diffusion electrode as the anode, and does not use an iridium oxide anode and a lead anode, effectively reducing the cost or reducing the pollution; (2) The present invention uses a diaphragm electrolytic cell to electrolytically synthesize glyoxylic acid under the condition that the pressure in the anode chamber is not lower than that in the cathode chamber, and the electrolytic voltage drops by about 1.6 V (compared with the iridium oxide anode), significantly reducing the energy consumption. (3) The product yield of the method for electrolytic reduction synthesis of glyoxylic acid in the present invention can be increased by about 6%. (IV) BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 , Schematic diagram of the electrolytic synthesis of glyoxylic acid with the oxidation reaction of hydrogen as the anodic reaction; O represents oxalic acid, R represents glyoxylic acid; A represents a membrane electrode, and B represents a gas diffusion electrode.
[0018] Figure 2 , Electrolytic reduction device diagram with the oxidation reaction of hydrogen as the anodic reaction; A represents a diaphragm electrolytic device, and B represents a non-diaphragm electrolytic device. (V) SPECIFIC EMBODIMENTS
[0019] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0020] Unless otherwise specified, the aqueous solutions of all experiments are prepared with deionized water; the pressures (atmospheric pressures) in the anode and cathode chambers are 1 atmosphere (1 atm).
[0021] In the following examples and comparative examples, the gas diffusion electrode (Pt loading is 0.1 - 0.5 mg / cm 2 ), the gas diffusion electrode (Pd loading is 0.3 mg / cm 2 ), the membrane electrode (Pt loading is 0.1 - 0.5 mg / cm 2 ) and the titanium-plated iridium oxide electrode (iridium content is 1 mg / cm 2 ) are all purchased from Hangzhou Sai'ao Electrochemical Instrument Co., Ltd.
[0022] The membrane electrode is composed of a gas diffusion layer, a catalytic layer and a cation exchange membrane, and the catalytic layer is located between the gas diffusion layer and the cation exchange membrane. Among them, the carbon cloth is the gas diffusion layer, the catalytic layer is composed of a platinum-carbon catalyst and a Nafion resin mixture, and the cation exchange membrane is a Nafion-117 membrane.
[0023] The gas diffusion electrode is composed of a gas diffusion layer and a catalytic layer. Among them, the carbon paper is the gas diffusion layer, and the catalytic layer is composed of a platinum-carbon catalyst, Nafion resin, and polytetrafluoroethylene resin mixed together.
[0024] Example 1: Gas diffusion anode - diaphragm electrolysis
[0025] Use Figure 2 The diaphragm electrolytic cell with the structure shown as A in [reference], the diaphragm electrolytic cell is successively divided into a gas chamber, an anode chamber, and a cathode chamber by an anode and a diaphragm. An anode is arranged between the gas chamber and the anode chamber, a diaphragm is arranged between the anode chamber and the cathode chamber, a cathode is arranged in the cathode chamber, and hydrogen gas is introduced into the gas chamber.
[0026] An aqueous solution containing 0.5 mol / L sulfuric acid is used as the anolyte (80 mL), and an aqueous solution containing 0.68 mol / L oxalic acid is used as the catholyte (60 mL); the gas diffusion electrode is used as the anode (area: 3.14 cm 2 , the Pt loading is 0.5 mg / cm 2 ), a lead sheet is used as the cathode (area: 6 cm 2 ), and a Nafion-324 membrane is used as the diaphragm. During the electrolysis process, the flow rate of hydrogen gas is controlled at 20 mL / min; the pressure of the anolyte is 1.01 atm, and the pressure of the catholyte is 1 atm. The temperatures of the catholyte and the anolyte are controlled at 10 °C, and an electrolysis is carried out by applying a current of 300 mA (the cathodic current density is: 5 A / dm 2 , the anodic current density is: 9.6 A / dm 2 ). After 8 hours of electrolysis, the electrolysis is stopped. The yield of glyoxylic acid in the catholyte is 90.1%, the average voltage is 6.0 V, the initial voltage is 5.8 V, and the voltage at the end of electrolysis is 6.3 V.
[0027] Examples 2 - 5: Electrolytic synthesis of glyoxylic acid under different anolyte pressures
[0028] Adopt the method of Example 1, change the pressure of the anolyte, and keep other operations the same. The experimental conditions and results are shown in Table 1.
[0029] Table 1 Results of electrolytic synthesis of glyoxylic acid under different anolyte pressures a
[0030] Example Anode hydraulic pressure Average voltage Initial voltage Final voltage Glyoxylic acid yield 2 1.0 atm 6.0V+0.6 5.8V 6.3+1.2V 90.2% 4 1.1 atm 6.1V 5.9V 6.4V 90.5% 4 2.0 atm 6.0V 5.8V 6.3V 90.4% 5 3.0 atm 6.0V 5.8V 6.3V 90.2%
[0031] a Other conditions not specified are the same as those in Example 1.
[0032] Examples 6 - 14: Effects of catalyst type and loading, electrolyte composition, current density, temperature, etc. on electrolytic reduction
[0033] Using the method of Example 1, electrolysis reactions were carried out under different catalyst types and loadings, electrolyte compositions, currents, and temperatures, with other operations being the same. The experimental conditions and results are shown in Table 2.
[0034] Table 2 Effects of catalyst type, electrolyte composition, current density, temperature, etc. on electrolytic reduction a
[0035]
[0036] Remarks: a Other unspecified conditions are the same as those in Example 1; S indicates that this condition is the same as that in Example 1.
[0037] Example 15, Membrane Electrode - Diaphragm Electrolysis
[0038] Using Figure 2 the diaphragm electrolytic cell with the structure shown as A in 2 , an aqueous solution containing 0.5 mol / L sulfuric acid was used as the anolyte (80 mL), and an aqueous solution containing 0.68 mol / L oxalic acid was used as the catholyte (60 mL); the membrane electrode was the anode (area: 3.14 cm 2 ), with a Pt loading of 0.5 mg / cm 2 ), a lead sheet was used as the cathode (area: 6 cm 2 ), and a Nafion-324 membrane was used as the diaphragm. During the electrolysis process, the flow rate of hydrogen was controlled at 20 mL / min; the anolyte pressure was 1.01 atm, and the catholyte pressure was 1 atm. The temperatures of the catholyte and anolyte were controlled at 10 °C, and a current of 300 mA was applied for electrolysis (cathode current density: 5 A / dm 2 , anode current density: 9.6 A / dm
[0039] Comparative Examples 1 - 3
[0040] According to the conditions in Table 3, using the method of Example 1, the anolyte pressure was changed to 0.9 atm as Comparative Example 1, and as a result, the average voltage increased by 3 V. The anode was changed to a titanium-plated iridium oxide electrode, the product yield decreased by about 6%, and as a result, the average voltage increased by 1.6 V, the noble metal consumption increased to 2 times the original, and the price increased to about 8 times the original. The anode was changed to a lead electrode, the product yield decreased by about 6%, and as a result, the average voltage increased by 2.3 V.
[0041] Table 3 Electrolytic synthesis results of glyoxylic acid under different anolyte pressures and different anodes a
[0042]
[0043] a S indicates being consistent with Example 1, and other unspecified conditions are also consistent with Example 1. / represents no hydrogen gas introduced.
[0044] Comparative Example 4, Gas Diffusion Electrode - Diaphragmless Electrolysis
[0045] Adopt Figure 2 The diaphragmless electrolytic cell with the structure shown as B in [reference], the diaphragmless electrolytic cell is divided into a gas chamber and an electrolytic chamber by the anode, an anode is arranged between the gas chamber and the electrolytic chamber, a cathode is arranged in the electrolytic chamber, and the gas chamber is used for introducing hydrogen gas.
[0046] Using an aqueous solution containing 0.68 mol / L oxalic acid as the electrolyte (60 mL); the gas diffusion electrode is the anode (area: 3.14 cm 2 , Pt loading is 0.3 mg / cm 2 ), and a lead sheet is the cathode (area: 6 cm 2 ). During the electrolysis process, the flow rate of hydrogen gas is controlled at 20 mL / min. The temperature of the electrolyte is controlled at 10 °C, and electrolysis is carried out by applying a current of 300 mA (cathode current density: 5 A / dm 2 , anode current density: 9.6 A / dm 2 ). After 2 hours of electrolysis, the voltage rises from 5.1 V to 9.9 V, and the electrolysis is stopped.
[0047] Compared with Example 1, the electrolysis voltage rises rapidly during the electrolysis process.
[0048] Comparative Example 5, Membrane Electrode - Diaphragmless Electrolysis
[0049] Adopt Figure 2 The diaphragmless electrolytic cell with the structure shown as B in [reference], using an aqueous solution containing 0.68 mol / L oxalic acid as the electrolyte (60 mL); the membrane electrode is the anode (area: 3.14 cm 2 , Pt loading is 0.5 mg / cm 2 ), and a lead sheet is the cathode (area: 6 cm 2 ). During the electrolysis process, the flow rate of hydrogen gas is controlled at 20 mL / min. The temperature of the electrolyte is controlled at 10 °C, and electrolysis is carried out by applying a current of 300 mA (cathode current density: 5 A / dm 2 , anode current density: 9.6 A / dm 2 ). After 2 hours of electrolysis, the voltage rises from 5.8 + 0.5 V to 7.9 V, and the electrolysis is stopped.
[0050] Compared with Example 15, the electrolysis voltage rises rapidly during the electrolysis process.
Claims
1. A method for electrolytic synthesis of glyoxylic acid, characterized in that, The described method uses a diaphragm electrolytic cell, with the oxidation reaction of hydrogen as the anodic reaction, the reduction reaction of oxalic acid as the cathodic reaction, an aqueous sulfuric acid solution as the anolyte, and an aqueous solution containing oxalic acid as the catholyte for electrolysis, and the electrolysis product in the catholyte is recovered to obtain the glyoxylic acid described above.
2. The method according to claim 1, wherein In the described diaphragm electrolytic cell, the pressure on the anolyte side of the diaphragm is greater than or equal to the pressure on the catholyte side of the diaphragm.
3. The method according to claim 2, wherein The pressure difference between the anolyte side and the catholyte side is 0 to 2 atm.
4. The method according to claim 3, wherein The pressure of the anolyte is 1 - 3 atm.
5. The method according to claim 1, wherein The described anodic reaction occurs on a gas diffusion electrode or a membrane electrode.
6. The method according to claim 5, characterized in that, The gas diffusion electrode is composed of a gas diffusion layer and a catalytic layer. The gas diffusion layer is a porous carbon material or metal material. The carbon material is carbon paper, carbon cloth, graphite felt, carbon felt or carbon foam. The metal material is titanium or silver. The catalytic layer is composed of a platinum-carbon or palladium-carbon catalyst and a binder. The binder is polytetrafluoroethylene resin or Nafion resin or a mixture of both. The platinum or palladium loading of the gas diffusion electrode is 0.1-0.5 mg / cm 2 .
7. The method according to claim 5, wherein The membrane electrode is composed of a gas diffusion layer, a catalytic layer, and a cation exchange membrane. The catalytic layer is located between the gas diffusion layer and the cation exchange membrane. The gas diffusion layer is a porous carbon material or a metal material. The carbon material is carbon paper, carbon cloth, graphite felt, carbon felt, or carbon foam. The metal material is titanium or silver. The catalytic layer is composed of a platinum-carbon or palladium-carbon catalyst and a binder. The binder is polytetrafluoroethylene resin, Nafion resin, or a mixture of the two. The cation exchange membrane is a sulfonic acid type cation exchange membrane. The platinum or palladium loading of the membrane electrode is 0.1 - 0.5 mg / cm 2 .
8. The method according to claim 1, wherein The diaphragm used in the described diaphragm electrolytic cell is a cation exchange membrane or a microporous membrane.
9. The method according to claim 1, wherein The described diaphragm electrolytic cell is successively divided into a gas chamber, an anodic chamber, and a cathodic chamber by an anode and a diaphragm. A cathode is provided inside the cathodic chamber, and the cathode uses a lead sheet. An aqueous solution containing 0.1 - 1.0 mol / L sulfuric acid is used as the anolyte; the flow rate of hydrogen is controlled at 20 mL / min; an aqueous solution containing 0.1 - 1.0 mol / L oxalic acid is used as the catholyte, and electrolysis is carried out at 0 - 30 °C and a cathodic current density of 2.5 - 10 A / dm 2 , and an anodic current density of 5 - 20 A / dm 2 under the conditions; the pressure on the anolyte side is 1 - 3 atm, and the pressure difference between the anolyte and the catholyte is 0 - 2 atm.